The Development of Earning Management in Indonesia: A Systematic Literature Review - Restuningdiah, Nurika; Sidharta, Eka Ananta (Asia Pacific Journal of Management and Education (APJME), 2023)
Management can affect the appearance of financial statements by earning management. Thus, the investors will be disturbed by earning management practice because the financial reports become incredible. There were mixed results and few systematic reviews in the research on earning management in Indonesia. Therefore, the objective of the research is to analyze the existing themes of earning management practices in Indonesia. The research method is guided by Reporting Standards for Systematic Evidence Syntheses review method to make a systematic review of the Sinta 1 and 2 databases. The research results of 23 eligible articles show four main themes in earning management in Indonesia: monitoring, management opportunities, accounting policies, and investor decision- making. The value of this research offers recommendations to future researchers to conduct more qualitative studies in earning management.